Efficacy and Safety of Intravenous Sodium Valproate in Convulsive Status Epilepticus in Children in Shahid Sadoughi Hospital - FALLAH, Razieh; YADEGARI, Yaser; SALMANI NODOUSHAN, Mahdi (Iranian Journal of Child Neurology, 2012)
How to Cite this Article: Fallah R, Yadegari Y, Salmani Nodushan M. Efficacy and Safety of Intravenous Sodium Valproate in Convulsive Status Epilepticus in Children in Shahid Sadoughi Hospital. Iran. J. Child. Neurol 2012;6(2):39-44. Objective Status epilepticus (SE) is the most common pediatric neurologic emergency with high mortality and morbidity. There is no consensus on the drug of choice in the treatment of children. The purpose of this study was to evaluate the clinical efficacy and safety of intravenous sodium valproate as a third-line drug in the treatment of generalized convulsive SE of children. Materials & Methods In a retrospective study, medical records of those children who were admitted to Shahid Sadoughi Hospital of Yazd due to refractory generalized convulsive SE and were treated by intravenous sodium valproate as a third-line drug from 2009 to 2011 were evaluated. Results Six girls and five boys with a mean age of 5.12 ± 1.2 years (range: 3 - 9.6 years) were evaluated. Intravenous valproate was effective for cessation of seizures in seven patients (63.6 %). The mean dose of valproate for stopping seizures was 27.1 ± 1.4 mg/kg/day. Children whose seizures were controlled by sodium valproate were older than non- responsive children (mean± SD: 4.8 ± 1.2 years vs. 3.1 ± 0.43 years, p= 0.03) and they also had shorter ICU stay days (mean± SD: 2.6 ± 1.4 days vs. 5.6 ± 2.8 days, p= 0.01). Two children had mild and transient nausea and vomiting. None of them had cardiopulmonary or severe paraclinical side effects. Conclusion Intravenous sodium valproate may be used as an effective and safe third-line antiepileptic drug in the treatment of pediatric generalized convulsive status epilepticus. References Raj D, Gulati S, Lodha R. Status epilepticus. Indian J Pediatr 2011;78(2):219-26. Shearer P, Riviello J. Generalized convulsive status epilepticus in adults and children: treatment guidelines and protocols. Emerg Med Clin North Am 2011;29(1):51-64. Mikati MA. Status epilepticus. In: Kliegman RM, Stanton BF, Schor NF, St. Geme JW, Behrman RE. Nelson textbook of pediatrics. 19th ed. Philadelphia: Saunders; 2011. P. 2013-7. Nair PP, Kalita J, Misra UK. Status epilepticus: Why, what, and how. J Postgrad Med 2011;57(3):242-52. Saz EU, Karapinar B, Ozcetin M, Polat M, Tosun A, Serdaroglu G et al. Convulsive status epilepticus in children: etiology, treatment protocol and outcome. Seizure 2011;20(2):115-8. Nam SH, Lee BL, Lee CG, Yu HJ, Joo EY, Lee J et al. The role of ketogenic diet in the treatment of refractory status epilepticus. Epilepsia 2011;52(11):e181-4. Shiloh-Malawsky Y, Fan Z, Greenwood R, Tennison M. Successful treatment of childhood prolonged refractory status epilepticus with lacosamide. Seizure 2011;20(7):586-8. Abend NS, Monk HM, Licht DJ, Dlugos DJ. Intravenous levetiracetam in critically ill children with status epilepticus or acute repetitive seizures. Pediatr Crit Care Med 2009;10(4):505-10. Chang YC, Lin JJ, Wang HS, Chou ML, Hung PC, Hsieh MY. Intravenous valproate for seizures in 137 Taiwanese children - valproate naive and non-naive. Acta Neurol Taiwan 2010;19(2):100-6. Wheless JW, Vazquez BR, Kanner AM, Ramsay RE, Morton L, Pellock JM. Rapid infusion with valproate sodium is well tolerated in patients with epilepsy. Neurology 2004;63(8):1507-8. Sofou K, Kristjánsdóttir R, Papachatzakis NE, Ahmadzadeh A, Uvebrant P. Management of prolonged seizures and status epilepticus in childhood: a systematic review. J Child Neurol 2009;24(8):918-26. Visudtibhan A, Bhudhisawadi K, Vaewpanich J, Chulavatnatol S, Kaojareon S. Pharmacokinetics and clinical application of intravenous valproate in Thai epileptic children. Brain Dev 2011;33(3):189-94. Kälviäinen R, Eriksson K, Parviainen I. Refractory generalised convulsive status epilepticus: a guide to treatment. CNS Drugs 2005;19(9):759-68. Arif H, Hirsch LJ. Treatment of status epilepticus. Semin Neurol 2008;28(3):342-54. Misra UK, Kalita J, Patel R. Sodium valproate vs phenytoin in status epilepticus: A pilot study. Neurology 2006;67(2):340-2. Kwan SY. The role of intravenous valproate in convulsive status epilepticus in the future. Acta Neurol Taiwan 2010;19(2):78-81. Aldenkamp A, Vigevano F, Arzimanoglou A, Covanis A. Role of valproate across the ages. Treatment of epilepsy in children. Acta Neurol Scand Suppl 2006;184:1-13. Limdi NA, Shimpi AV, Faught E, Gomez CR, Burneo JG. Efficacy of rapid IV dministration of valproic acid for status epilepticus. Neurology 2005;64(2);353-535. Morton LD, O’Hara KA, Coots BP, Pellock JM. Safety of rapid intravenous valproate infusion in pediatric patients. Pediatr Neurol 2007;36(2):81-83. Yu KT, Mills S, Thompson N, Cunanan C. Safety and efficacy of intravenous valproate in pediatric status epilepticus and acute repetitive seizures. Epilepsia 2003;44(5):724-6. Trinka E. The use of valproate and new antiepileptic drugs in status epilepticus. Epilepsia 2007;48 Suppl 8:49-51. Chen L, Feng P, Wang J, Liu L, Zhou D. Intravenous sodium valproate in mainland China for the treatment of diazepam refractory convulsive status epilepticus. J Clin Neurosci 2009;16(4):524-6. Mehta V, Singhi P, Singhi S. Intravenous sodium valproate versus diazepam infusion for the control of refractory status epilepticus in children: a randomized controlled trial. J Child Neurol 2007;22(10):1191-7. Jha S, Jose M, Patel R. Intravenous sodium valproate in status epilepticus. Neurol India 2003;51(3):421-2. Kanner AM. Intravenous valproate for status epilepticus. An effective, yet still merely empirical alternative! Epilepsy Curr 2008;8(3):66-7. Russell S. Carnitine as an antidote for acute valproate toxicity in children. Curr Opin Pediatr 2007;19(2):206- 10. Gilad R, Gilad R, Izkovitz N, Dabby R, Rapoport A, Sadeh M, et al. Treatment of status epilepticus and acute repetitive seizures with i.v. valproic acid vs. phenytoin. Acta Neurol Scand 2008;118(5):296-300.